A Schematic Overview of Securing Precision Medicine Data with a DNA Database System - Conley, Shannon; Kaya, Mehmet; Varol, Asaf (Fırat University, 2017)
This work explores the security challenges facing the implementation of the National Institute of Health’s proposed Precision Medicine Initiative® Cohort Program. The program is planning to recruit over a million participants and collect their health data over an extended period of time. Data will be made available to researchers to drive the development of more “precise preventive care and medical treatment”. However, the ability of the program to keep participants’ personal health information private is being scrutinized and might deter volunteer recruitment. This is due in large part to recent security breaches experienced by the US federal government in which over 20 million people’s security clearance data was stolen including credit card numbers and fingerprints. To secure the personal information of the volunteers, we propose the use of a natural computing nature-inspired hardware technique: molecular data storage. In this scheme, personal patient identifiers would be encoded and stored in DNA molecules, thus protected behind a “biological firewall”. The DNA database would only be accessed in the same laboratory environment(s) used to collect/process patient health samples and data would be retrieved using enzyme-based biological reactions. An anonymous volunteer id randomly assigned to each volunteer would be stored both in the DNA database and a traditional network connected database(s) used by program approved researchers and serve as the cross-reference key between databases. By adopting the technique, the new initiative could not only revolutionize the way medicine is practiced, but also the field of data storage and security

Bu çalışma Ulusal Sağlık Enstitüsü tarafından önerilen Hassas Tıp Projesi’nin (Precision Medicine Initiative) uygulanmasında karşılaşılabilecek güvenlik sorunlarını araştırmaktadır. Bu projede bir milyondan fazla katılımcıya ulaşıp belli bir zaman sürecinde bu katılımcıların sağlık verilerinin toplanması planlanmaktadır. Bu veriler daha sonra “daha hassas önleyici bakım ve tıbbi müdahale” teknikleri geliştirmek amacı ile araştırmacın erişimine sunulacaktır. Ancak bu proje katılımcıların kişisel ve özel sağlık bilgilerinin gerektiği şekilde korunması yönünden eleştirilmektedir ve insanlar kişisel bilgilerinin güvenliğinden şüphe ederek programa katılımda gönülsüz kalabilirler. Birleşik Devletler Federal Hükümetinin yakın zamanda tecrübe ettiği ve 20 milyondan fazla insanın kredi kartı numaraları ve parmak izi gibi güvenlik bilgilerinin çalındığı bir güvenlik sorunu da aslında kısmen bu duruma neden olmaktadır. Bu çalışmada sunulan şemada, kişisel hasta numaralarının kodlanıp DNA molekülleri içinde saklanarak bir “biyolojik güvenlik duvarı” ile korunması öngörülmektedir. Bu DNA veri tabanı sadece hasta örneklerinin toplanıp işlendiği laboratuvarda erişilebilecek ve veriler sadece enzim-bazlı biyolojik reaksiyonlar vasıtası ile tekrar elde edilebilecektir. Her katılımcıya rastgele atanan anonim bir katılımcı numarası hem DNA veri tabanında hem de programda akredite edilmiş araştırmacıların kullandığı ve veri tabanları arasında çapraz başvuru sağlayan geleneksel elektronik bir veri tabanında saklanacaktır. Bu tekniğin kullanılması ile, bu hassas tıp projesi sadece tıp uygulamalarında değil, veri depolama ve güvenlik alanlarında da çok büyük yenilikler başarabilir.
Hassas Tıp Verilerini Bir DNA Veritabanı Sistemiyle Güvenceye Almaya Şematik Bir Bakış